A multi-signal fluorescent probe for simultaneously distinguishing and sequentially sensing cysteine/homocysteine, glutathione, and hydrogen sulfide in living cells. Issue 9 (13th July 2017) - He, Longwei; Yang, Xueling; Xu, Kaixin; Kong, Xiuqi; Lin, Weiying
Abstract : A multi-signal fluorescent probe was engineered for simultaneously distinguishing and sequentially sensing cysteine/homocysteine, glutathione, and hydrogen sulfide in living cells. Abstract : Biothiols, which have a close network of generation and metabolic pathways among them, are essential reactive sulfur species (RSS) in the cells and play vital roles in human physiology. However, biothiols possess highly similar chemical structures and properties, resulting in it being an enormous challenge to simultaneously discriminate them from each other. Herein, we develop a unique fluorescent probe (HMN ) for not only simultaneously distinguishing Cys/Hcy, GSH, and H2 S from each other, but also sequentially sensing Cys/Hcy/GSH and H2 S using a multi-channel fluorescence mode for the first time. When responding to the respective biothiols, the robust probe exhibits multiple sets of fluorescence signals at three distinct emission bands (blue-green-red). The new probe can also sense H2 S at different concentration levels with changes of fluorescence at the blue and red emission bands. In addition, the novel probeHMN is able to discriminate and sequentially sense biothiols in biological environments via three-color fluorescence imaging. We expect that the development of the robust probeHMN will provide a powerful strategy to design fluorescent probes for the discrimination and sequential detection of biothiols, and offer a promising tool for exploring the interrelated roles of biothiols in various physiological and pathological conditions.